2022
DOI: 10.1002/cbin.11963
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin and xanthohumol counteract the TNFα‐mediated activation of endothelial cells through the inhibition of the NF‐κB signaling pathway

Abstract: Angiogenesis, a process characterized by the formation of new blood vessels from pre-existing ones, is a crucial step in tumor growth and dissemination. Given the ability of tumors to interfere with multiple or different molecular pathways to promote angiogenesis, there is an increasing need to therapeutically block tumor progression by targeting multiple antiangiogenic pathways. Natural polyphenols present health-protective properties, which are likely attributed to their ability to activate multiple pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Xhantohumol and nobiletin, are the most abundant flavonoids extracted respectively from the hop plant and red-orange. Recently, authors showed the effects of these two compounds on colon cancer cells, demonstrating that they sensitize colorectal cancer stem cells to 5-fluorouracil (5-Fu) and oxaliplatin (FOX)-based chemotherapy and affect angiogenesis [26,27].…”
Section: Flavonoids and Cancer: Role Of Nf-κb Signaling Pathwaymentioning
confidence: 99%
“…Xhantohumol and nobiletin, are the most abundant flavonoids extracted respectively from the hop plant and red-orange. Recently, authors showed the effects of these two compounds on colon cancer cells, demonstrating that they sensitize colorectal cancer stem cells to 5-fluorouracil (5-Fu) and oxaliplatin (FOX)-based chemotherapy and affect angiogenesis [26,27].…”
Section: Flavonoids and Cancer: Role Of Nf-κb Signaling Pathwaymentioning
confidence: 99%
“…In the light of the strict interconnections between IBD, oxidative stress and inflammation and considering the anti-oxidative and anti-inflammatory properties of PMF and PF, we here investigated whether these polyphenols subclasses, alone or in combination, display protective effects in an in vitro model of IBD. To this aim, we used selected fractions of PMF (PMFF) and PF (PFF) isolated from the extracts of Citrus sinensis and Humulus lupulus respectively, either alone or in combination (MIX) as elsewhere reported [ 44 , 45 ]. Moreover, differentiated Caco-2 cells, an established model of the human intestinal barrier, were exposed to IL-1β either in the absence or in the presence of PMFF or PFF or MIX.…”
Section: Introductionmentioning
confidence: 99%